Multi-plume sprays interacting with subsonic compressible gas jets. (15th March 2017) - Ghasemi, Abbas; Pereira, Aaron; Li, Xianguo; Ren, Yi
Highlights: Multi-plume sprays injected in subsonic compressible cross-flow jets are studied. Simulated spray topology and the volumetric shadowgraphy images agree well. Numerically predicted droplet velocities agree well with the PIV measurements. Presence of the cross-flow jet produces finer droplet sizes in a shorter time. Velocity and pressure field of the cross-flow jet is altered by multi-plume spray. Abstract: Injection of multi-plume sprays into subsonic compressible cross-flow jets is commonly encountered in practical applications and it is investigated experimentally and computationally in this study for the Mach numbers of 0.35 and 0.58. It is shown that comparing with the volumetric shadowgraphy images, the instantaneous topology of the sprays issued into the cross-flowing jets is well resolved by the present large eddy simulation (LES) with the Eulerian-Lagrangian multiphase formulation. The droplet velocities obtained from the simulations compare well with the particle imaging velocimetry (PIV) measurements. Compared to the multi-plume spray evolution in a stagnant ambient, the presence of the cross-flow jet is found to accelerate the break-up and produce smaller droplets. The individual spray plumes are found to penetrate symmetrically with respect to the central plane of the cross-flow jet. The penetration of the multi-plume sprays into the core of the cross-flows is shown to alter the velocity and pressure field of the compressible jet.